MENGATASI KENAKALAN REMAJA PADA MASA TRANSISI - Erhan Syah Albanjari (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2018)
The teenage transition period is a period of change in behavior that is felt differently. Teenagers have conditions and energy that are very prime and have the potential and reality of fighting spirit and high power of patriotism. In this transition period, adolescents must be conditioned in a positive direction so that adolescents grow into mature adults who behave noble. The transitional period of adolescents is prone to delinquency, both those with the potential for criminal acts and ordinary crime. In many cases events that occur many parents who complain, even troubled, because their children who had stepped on the early teens became stubborn, difficult to manage, young huffed and daydreaming. In the context of the behavior of students at school, the ability of the teacher to carry out his role well, forming the personal of the students so that they grow well, very necessary in the learning process that is right for these students. The role of the teacher must be in the form of guidance services for those who experience difficulties in the transition stage, which in its development is one of the special handling. This means that students who are classified as having problems at the top level need to be prioritized. The reason for choosing the right approach by the teacher is that the transition difficultiesexperienced by the child can be handled optimally and the teacher recognizes the true disturbances. For this reason, efforts to overcome adolescent behavior during this transition period can be carried out preventive, curative and refresive efforts. Through the approach to Islamic education carried out with a general effort namely Islamic education during the womb, after birth given love and environmental education in the family and in the community. Special efforts are carried out with supervision, guidance and counseling as well as specific actions that are justified by the applicable legislation